Lectotypification and new data on the distribution of the Philippine endemic Liparis dumaguetensis (Orchidaceae) - Fulgencio, Bea Katrina R.; Cootes, Jim; Amparado, Olive A.; Naive, Mark Arcebal K. (Phytotaxa, 2024)
Liparis dumaguetensis (Orchidaceae) is a Philippine endemic species widely distributed throughout the Philippine archipelago. A review of literature and specimens demonstrated the necessity for lectotypification of this species which we accomplished in this paper. Further, detailed information is provided based on our current collection such as a description, colour photographs, an updated geographical distribution, habitat, phenology, and an IUCN conservation assessment.